Going clear : Scientology, Hollywood, and the prison of belief - Wright, Lawrence, 1947- (Alfred A. Knopf, 2013)
"Based on more than two hundred personal interviews with both current and former Scientologists--both famous and less well known--and years of archival research, Lawrence Wright uses his extraordinary investigative skills to uncover for us the inner workings of the Church of Scientology: its origins in the imagination of science-fiction writer L. Ron Hubbard; its struggles to find acceptance as a legitimate (and legally acknowledged) religion; its vast, secret campaign to infiltrate the U.S. government; its vindictive treatment of critics; its phenomenal wealth; and its dramatic efforts to grow and prevail after the death of Hubbard"--From publisher description.